Systematic Literature Review on Data Security and Privacy for e-Government - Mela Firdini Azzahra; Ardhan Aghsal Dwi Putra; Jingga Mustika Putri; Maulana Aditya; Risqy Siwi Pradini (Institut Teknologi, Sains, dan Kesehatan RS.DR. Soepraoen Kesdam V/BRW, 2026)
The use of e-Government is increasing along with efforts to improve the efficiency, transparency, and quality of public services. However, advances in digitalization are also accompanied by cybersecurity risks and threats to data privacy. This study aims to examine the implementation of data security and privacy in e-Government, as well as evaluate the technologies used to mitigate data leaks and misuse. The method used is Systematic Literature Review of articles published between 2021 and 2025 through Scopus, ScienceDirect, and Google Scholar databases. The research selection followed the PRISMA 2020 guidelines, resulting in 16 articles meeting the eligibility criteria. The study findings indicate that information security implementation in government institutions remains inconsistent, with key challenges related to weak security management, technical system vulnerabilities, and low public trust in personal data protection. Several technologies considered to have potential to improve security include blockchain, advanced cryptography, and automation for vulnerability detection, although their implementation remains hampered by cost, scalability, and human resource readiness. Overall, this study emphasizes that a comprehensive approach that combines technology, management, and increased security awareness is needed to strengthen data protection in e-Government.